Corporate Infrastructure Management Affecting Intellectual Capital - Dudi Haryadi (Almana : Jurnal Manajemen dan Bisnis, 2020)
To support the success of company activities, it is necessary to complete facilities and reliable infrastructure. This paper aims to review and analyze concepts, definitions, research models, and development of infrastructure management models and intellectual capital from several pieces of literature that have been implemented in various companies. The writing approach used is to conduct a literature study that reviews the concepts and explains them. This paper also tries to describe the relationship or influence between infrastructure management and intellectual capital. Academically this paper is useful for the development of conceptual models in the direction of research and research discourse that is developed, as well as providing an understanding and in-depth understanding of the conception of infrastructure management and intellectual capital. Being an effective HR professional doesn't just change from operational work to strategy. This means learning to master the operational and strategic processes and people. Success in this role requires an understanding of the results, metaphors, and specific actions in each role. The role of corporate infrastructure management in shaping an efficient corporate infrastructure is as an administrative expert who can help in reducing unnecessary costs, increasing efficiency, and continuously finding new ways to work better.